Samarinda Grabbike Driver’s Income Analysis in 2019 - Partha, Made Ngurah; Ellyawati, Noor; Safitri, Komang Ayu (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2021)
This research purposes to determine the income of Grabbike drivers in Samarinda during March 2019 and to compare the income toward the City Minimum Wage (UMK) in 2019. This research also intends to know the average and the percentage of Grabbike driver’s income in Samarinda toward the City Minimum Wage (UMK) in 2019. This is a descriptive quantitative research. The populations in this research are 1200 Samarinda Grabbike drivers in 2019 with 120 respondents. Data collection techniques in this research use questionnaires, interviews and documentation. The data analysis technique uses the net income formula; the average and percentage income. The research data and analysis of the Samarinda Grabbike driver’s income in 2019 includes several indicators; the number of working hours and working days. The research results show that the Samarinda Grabbike driver’s net income in March 2019 is Rp. 200,758,204. The percentage comparison between Samarinda Grabbike Driver’s incomes toward the City Minimum Wage (UMK) shows 24 drivers achieving high-level income or 20%, 65 drivers achieving medium-level income or 54.2% and 31 drivers achieving low-level income or 25.8%. The average income of Samarinda Grabbike drivers in March 2019 is Rp. 1,672,985.